Tvarumo ir darnos veiksniai planuojant urbanistinę plėtrą - Daunora, Zigmas Jonas (Journal of Architecture and Urbanism, 2010)
Factors of sustainability and harmony in planning urban development The paper discusses conceptual differences of the definitions “sustainability” and “harmony” and the confusion caused by incorrect interpretations of sustainable development strategies. The paper also deals with gaps in urban design and planning standardization, which becomes a serious obstacle to sustainable urban and regional development. The priority targets indicated in this paper are: 1) urban design normative validation; 2) differential definition of urban structural areas development; 3) establishment of detailed urban central part formation and 4) integrated planning of the suburban and metropolitan range area. Article in Lithuanian. Santrauka. Svarstomi tvarumo (sustainability) ir darnos (harmony) sąvokų skirtumai ir dėl jų painiojimo atsirandančios netikslios sustainable development strategijos interpretacijos. Aptariamos urbanistinio projektavimo ir planavimo norminimo spragos, tampančios rimtu kliuviniu tvariai miestų ir rajonų urbanistinei plėtrai. Nurodoma, kad prioritetiniai uždaviniai yra: 1) urbanistinio projektavimo normyno įteisinimas; 2) diferencijuotas miesto struktūrinių dalių plėtros apibrėžimas; 3) detalizuotas miesto centrinės dalies formavimo numatymas; 4) integruotas priemiesčio zonos arba metropolinio arealo planavimas. Reikšminiai žodžiai: tvari plėtra, struktūra, urbanistinis projektavimas ir planavimas, terminologija. First Published Online: 22 May 2013